THE INFLUENCE OF BEHAVIOR INTENTION, PERSONAL AUTONOMY, ACCESSIBILITY OF INFORMATION, AND SOCIAL SUPPORT ON THE COMPLIANCE OF THE USE OF PPE AT PT. PLN - Fanny Tri Cahyani; Sri Widati (Universitas Airlangga, 2021)
The International Labor Organization states that more than 250,000,000 workplace accidents, more than 160,000,000 become ill because of hazards caused by the workplace, and 1,200,000 workers died due to their workplaces each year. Workplaces that have high levels of danger can cause harm to workers, and thus, companies as well. One effort to reduce the risk of danger is the use of Personal Protective Equipment (PPE). Compliance with the use of PPE is influenced by many factors. This study aims to analyze the influence of behavioral intention, personal autonomy, accessibility of information, and social support in complying with the use of PPE. This study was analytic observational and used the cross-sectional research design. The population of this research, amounting to 44 workers, were all employees at PT. PLN. The sample size was 41 samples selected using the simple random sampling method. This study shows (1) behavioral intention had no effect on compliance with the use of PPE (sig.= 0.581), and (2) personal autonomy had no effect on compliance with the use of PPE (sig. = 0.075). Meanwhile, (3) social support had no effect on compliance with the use of PPE (sig. = 0.575). However, accessibility of information affected the use of PPE (sig. = 0.042). To maintain compliance with the use of PPE, researchers suggest to continue health promotion, conduct monitors, and implement a reward and punishment system for workers.Keywords: accessibility of information, behavior intention, personal autonomy, personal protective equipment, social support